OVERVIEW OF THE MODERN WORLD ENERGY MARKET - Perevozova, I.V.; Morozova, O.S.; Sakun , A.Zh.; Mainka , M.K. (The actual problems of regional economy development, 2022)
With the beginning of the industrial age, the ability to use different types of energy has changed the living conditions of billions of people, allowing them to enjoy an unprecedented level of comfort and mobility. The need for a profound transformation of the world's energy infrastructure is widely recognized due to growing concerns about global climate change. The article considers the main trends in the global energy market, typical for the end of 2021 - early 2022, identifies countries with the best energy balance and describes the process of transition to a low-carbon energy system. A special place in the article is occupied by the distribution of energy sources by differentiating their characteristics and changing approaches to their value, use in the world and a certain time range, summarizes the main trends in each fuel. In recent years, the steady increase in energy consumption has been closely linked to the growth of prosperity and economic opportunities in much of the world. However, at this stage of human existence there is a huge energy problem. This challenge has at least two critical dimensions. Predominant dependence on fossil fuels, in particular, threatens to change the Earth's climate to such an extent that it can have serious consequences for the integrity of both natural systems and vital human systems. At the same time, much of the world's population still does not have access to one or more basic energy and related services, such as clean fuel for cooking and transportation. In addition, this article describes the prospects for the development of major energy markets and technological trends, as well as describes the impact of international energy markets on macroeconomic indicators. Based on their research, scenarios for the development of hydrocarbon companies in the process of energy transition of the world economy to a low-carbon energy system are outlined.